2018
DOI: 10.1091/mbc.e18-05-0315
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple determinants and consequences of cohesion fatigue in mammalian cells

Abstract: Cells delayed in metaphase with intact mitotic spindles undergo cohesion fatigue, where sister chromatids separate asynchronously, while cells remain in mitosis. Cohesion fatigue requires release of sister chromatid cohesion. However, the pathways that breach sister chromatid cohesion during cohesion fatigue remain unknown. Using moderate-salt buffers to remove loosely bound chromatin cohesin, we show that “cohesive” cohesin is not released during chromatid separation during cohesion fatigue. Using a regulated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…4b). These observations are consistent with "cohesion fatigue", a phenomena where sustained microtubule pulling forces exerted during mitotic arrest drive unscheduled chromosome segregation prior to anaphase onset 20,21 . We interpret these data to indicate the moderate and severe conditions represent a phenotypic continuum of cohesion fatigue as sister chromatids are progressively separated during mitotic arrest.…”
Section: Lethal Replication Stress Induces Cohesion Fatiguesupporting
confidence: 78%
“…4b). These observations are consistent with "cohesion fatigue", a phenomena where sustained microtubule pulling forces exerted during mitotic arrest drive unscheduled chromosome segregation prior to anaphase onset 20,21 . We interpret these data to indicate the moderate and severe conditions represent a phenotypic continuum of cohesion fatigue as sister chromatids are progressively separated during mitotic arrest.…”
Section: Lethal Replication Stress Induces Cohesion Fatiguesupporting
confidence: 78%
“…Cohesion fatigue could elevate chromosome mis-segregation because of effects on centromeric geometry or flexibility that might increase merotelic attachment rate ( Sakuno et al., 2009 ). It has also been suggested that stretched inter-kinetochore distance seen in mild cohesion fatigue (i.e., before complete PSCS) could displace high inner centromeric aurora B, leading to increased incidence of merotelic attachment ( Sapkota et al., 2017 ). Alternatively, because multiple studies have demonstrated an intricate interplay between chromosome cohesion factors and regulation of the chromosomal passenger complex (CPC), responsible for error correction (reviewed in Trivedi and Stukenberg, 2016 , Mirkovic and Oliveira, 2017 , Kleyman et al., 2014 ), it is possible that cohesion fatigue might prevent efficient correction of mal-attachments by improper regulation of the CPC.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that Wapl depletion restores proper strength of centromeric cohesion in the absence of INCENP-HP1 interaction. In contrast, a recent study showed that Wapl-mediated opening of cohesin rings is not required after metaphase arrest to separate sister chromatid in cohesion fatigue (89). Thus, it seems that the sister chromatid cohesion defects in cells lacking INCENP-HP1 interaction are not simply an accelerated cohesion fatigue defect.…”
Section: Discussionmentioning
confidence: 84%